2021
DOI: 10.1186/s13287-021-02312-x
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide promotes proliferative and osteogenic potentials of human placenta-derived mesenchymal stem cells through the activation of Wnt/β-catenin signaling

Abstract: Introduction The in vitro expansion and differentiation of mesenchymal stem cells derived from bone marrow (BM-hMSCs) are considered as potential therapeutic tools for clinical applications in bone tissue engineering and regenerative medicine. However, invasive sampling and reduction in number and proliferative capacity with age are the major limitations of BM-hMSCs. Recently, human placenta-derived MSCs (PL-hMSCs) obtained by a non-invasive procedure have attracted much interest. Attempts to i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Activation of Wnt/β-catenin promotes osteogenesis while suppressing adipogenesis as it enhances the expression of transcription factor RUNX2 and reduces the expression of PPARγ. , On the other hand, Wnt is inhibited by several molecules such as DKK1 and WNT5B, resulting in the activation of PPARγ to enhance the adipogenic differentiation of MSCs . In a previous study, AP has been shown to promote the osteogenic differentiation lineage of MSCs by activating the Wnt signaling pathway and increasing RUNX2 expression . This is consistent with our study in which AP showed an inhibitory effect on the gene expression of DKK1 , WNT5B , and PPARγ .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Activation of Wnt/β-catenin promotes osteogenesis while suppressing adipogenesis as it enhances the expression of transcription factor RUNX2 and reduces the expression of PPARγ. , On the other hand, Wnt is inhibited by several molecules such as DKK1 and WNT5B, resulting in the activation of PPARγ to enhance the adipogenic differentiation of MSCs . In a previous study, AP has been shown to promote the osteogenic differentiation lineage of MSCs by activating the Wnt signaling pathway and increasing RUNX2 expression . This is consistent with our study in which AP showed an inhibitory effect on the gene expression of DKK1 , WNT5B , and PPARγ .…”
Section: Discussionsupporting
confidence: 91%
“…The expression of specific surface markers of hBM-MSCs was evaluated by flow cytometry (FACScalibur, Becton Dickinson, USA), as previously described . Briefly, after trypsinization, cells were suspended in PBS and incubated for 30 min at 4 °C in the dark with antihuman monoclonal antibodies including PE-conjugated anti-CD34 antibody, PE-conjugated anti-CD73 antibody, PE-conjugated anti-CD90 antibody, PE-conjugated anti-CD105 antibody, and FITC-conjugated anti-CD45 antibody (Bio Legend, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, osteoblast's differentiation markers were evaluated by measuring Runx2, Osx, OPG, COL1A1 and OCN. Runx2 and Osx are transcription factors that act downstream of the Wnt/βcatenin signaling in transcribing the bone-forming genes OPG, COL1A1, and OCN [74,75]. DEXA injections revealed a significant decrease in the expression levels of bone Runx2 and Osx and their downstream targets (COL1A1, OCN, and OPG), indicating a deactivated osteoblasts Wnt/β-catenin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of Wnt proteins, such as Wnt3a and Wnt5a, which are inducers of osteo/cementoblastic differentiation [16,17], was eliminated in the Osteocalcin-expressing cells of conditional knockout mice of Wntless [15]. Osteocalcin was shown to be specifically expressed in cells differentiating towards or differentiated osteo/cementoblastic lineage cells, but was negligible in stem cells [18]; however, it was expressed in PDLF [19]. In the periodontal tissue of conditional knockout mice of Wntless, the periodontal ligament and cementum were wider, the alveolar bone was narrower, and the expression of osteogenic markers, such as Alp, Runx2, and Osterix, was downregulated [15].…”
Section: Introductionmentioning
confidence: 99%